2005
DOI: 10.1109/tps.2005.844615
|View full text |Cite
|
Sign up to set email alerts
|

Trapping and acceleration of nonideal injected electron bunches in laser Wakefield accelerators

Abstract: Most conceptual designs for future laser wakefield accelerators (LWFA) require external injection of precisely-phased, monoenergetic, ultrashort bunches of MeV electrons. This paper reports simulation and Hamiltonian models of several nonideal injection schemes that demonstrate strong phase bunching and good accelerated beam quality in a channel-guided LWFA. For the case of monoenergetic, unphased (long bunch) injection, there is an optimum range of injection energies for which the LWFA can trap a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…19,20 In those simulations, the minimum injection energy for trapping W − was 1.0 MeV, which was significantly below the theoretical uniform plasma value of 1.6 MeV. However, the presence of the experimentally found long density ramp caused W − to increase to approximately 4 MeV.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…19,20 In those simulations, the minimum injection energy for trapping W − was 1.0 MeV, which was significantly below the theoretical uniform plasma value of 1.6 MeV. However, the presence of the experimentally found long density ramp caused W − to increase to approximately 4 MeV.…”
mentioning
confidence: 79%
“…In a uniform plasma, this accelerating and focusing region corresponds to exactly one-quarter of the wave period. In a plasma channel with no axial variation in density, recent analytical and simulation studies have shown 19,20 that the channel introduces a favorable shift in the wakefield phases that are both focusing and accelerating, thereby reducing the minimum injection energy for trapping and increasing allowable acceleration ͑dephasing͒ length and final energy.…”
mentioning
confidence: 99%
“…However, under the conditions explored in this article, an analytical approximation of the wakefield can be made. 11,[26][27][28] The main restriction is that the laser intensity is relatively low. Under this condition the plasma wave can be described by simple harmonics.…”
Section: Plasma Wave Descriptionmentioning
confidence: 99%
“…As a result, the trapping conditions which can be derived from the Hamiltonian are largely the same. This differs from the case when electrons are injected behind the laser pulse [37,66] and suddenly enter the wakefield. In this case, the injection phase will determine the strength of the wakefield the electrons suddenly experience.…”
Section: Comparison With Injection At An Anglementioning
confidence: 85%
“…The dependence of the collection efficiency on the injection angle becomes stronger for larger injection energies. In general one can obtain a better combination of collection efficiency and energy spread with injection at an angle than with bunch injection behind the laser pulse [37,40,66]. The rms energy spread after acceleration in a 6 cm long channel is relatively low and decreases with the injection angle, while the mean energy after acceleration in the wakefield grows with the angle.…”
Section: Effect Of the Anglementioning
confidence: 99%